Canine Melanoma Immunology and Immunotherapy: Relevance of Translational Research - Tarone, Lidia; Giacobino, Davide; Camerino, Mariateresa; Ferrone, Soldano; Buracco, Paolo; Cavallo, Federica; Riccardo, Federica (Frontiers in Veterinary Science, 2022)
In veterinary oncology, canine melanoma is still a fatal disease for which innovative and long-lasting curative treatments are urgently required. Considering the similarities between canine and human melanoma and the clinical revolution that immunotherapy has instigated in the treatment of human melanoma patients, special attention must be paid to advancements in tumor immunology research in the veterinary field. Herein, we aim to discuss the most relevant knowledge on the immune landscape of canine melanoma and the most promising immunotherapeutic approaches under investigation. Particular attention will be dedicated to anti-cancer vaccination, and, especially, to the encouraging clinical results that we have obtained with DNA vaccines directed against chondroitin sulfate proteoglycan 4 (CSPG4), which is an appealing tumor-associated antigen with a key oncogenic role in both canine and human melanoma. In parallel with advances in therapeutic options, progress in the identification of easily accessible biomarkers to improve the diagnosis and the prognosis of melanoma should be sought, with circulating small extracellular vesicles emerging as strategically relevant players. Translational advances in melanoma management, whether achieved in the human or veterinary fields, may drive improvements with mutual clinical benefits for both human and canine patients; this is where the strength of comparative oncology lies.